MOVES ANALYSIS OF APPLICATION LETTERS WRITTEN BY AGRIBUSINESS STUDENTS (A DESCRIPTIVE STUDY AT ESP CLASS) - Dedeh Rohayati (Universitas Galuh, 2018)
This study aimed at 1) analyzing moves of Application Letter written by Agribusiness students; and 2) language used in Application Letter. The study adopted the descriptive research involving the third semester students at Agribusiness Department of Agriculture Faculty in a Private University in East Priangan, West Java. The selected participants were 18 students who were asked to write Application Letter (solicited letter); and those document texts were analyzed, particularly, in term of the move structure referring to previous study conducted by Bhatia (1993), Henry and Roseberry (2001), Khan & Tin (2012), and Wijayanti (2017), by using quantitative and qualitative descriptive method. Therefore, the present study provided evidence for description of moves in Application Letter written by Agribusiness students. It consisted of fourteen moves: opening salutation, referring to source information, stating reason, offering candidature, introducing candidature, promoting candidature, offering candidature, glorifying institution, enclosing document, willingness to action, stressing the fact, offering to provide information, thanking, and closing salutation. However, the move structure was weakened by their inability in producing effective and impressive language used in Application Letter; they still need improving in language aspect such as expression, cohesive, coherence, and spelling. This resulted in necessity of an explicit teaching in writing professional genre of Application Letter for Agribusiness students. Further research is recommended to investigate the related topic in terms of language aspect.Key words: Agribusiness Students, Application Letter, ESP, Moves Analysis